2016
DOI: 10.1016/j.drugalcdep.2015.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Variation in CYP2A6 and tobacco dependence throughout adolescence and in young adult smokers

Abstract: Background-Smoking is influenced by genetic factors including variation in CYP2A6 and CYP2B6, which encode nicotine-metabolizing enzymes. In early adolescence, CYP2A6 slow nicotine metabolism was associated with higher dependence acquisition, but reduced cigarette consumption. Here we extend this work by examining associations of CYP2A6 and CYP2B6 with tobacco dependence acquisition in a larger sample of smokers followed throughout adolescence.Methods-White participants from the Nicotine Dependence in Teens co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
(66 reference statements)
0
14
0
1
Order By: Relevance
“…O'Loughlin et al (2004) followed 228 nondependent smokers in grade seven over approximately 30 months and found that individuals with less active genetic variants in CYP2A6 were more likely to develop nicotine dependence but smoked fewer cigarettes per day once dependent. In a follow-up study examining 421 adolescents who had ever smoked a cigarette, Chenoweth et al (2016) similarly found that slow metabolism conferred by CYP2A6 variation was associated with increased risk of nicotine dependence in adolescence. Huang et al (2005) examined variation in CYP2A6 in 1518 adolescents enrolled in a longitudinal study in the United Kingdom and similarly found that individuals with variants associated with slower metabolism were more likely to be current versus former smokers at age 18 years compared with normal metabolizers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…O'Loughlin et al (2004) followed 228 nondependent smokers in grade seven over approximately 30 months and found that individuals with less active genetic variants in CYP2A6 were more likely to develop nicotine dependence but smoked fewer cigarettes per day once dependent. In a follow-up study examining 421 adolescents who had ever smoked a cigarette, Chenoweth et al (2016) similarly found that slow metabolism conferred by CYP2A6 variation was associated with increased risk of nicotine dependence in adolescence. Huang et al (2005) examined variation in CYP2A6 in 1518 adolescents enrolled in a longitudinal study in the United Kingdom and similarly found that individuals with variants associated with slower metabolism were more likely to be current versus former smokers at age 18 years compared with normal metabolizers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Audrain-McGovern (2007) examined 222 adolescent ever-smokers of European ancestry and found that normal CYP2A6 metabolizers developed symptoms of dependence at a faster rate than slower CYP2A6 metabolizers. Other studies suggest that the increased risk of slower metabolizers for developing nicotine dependence in adolescence disappears by young adulthood (Chenoweth et al, 2016). Cannon et al (2016) followed 296 participants across ages 16-24 years and found that using a CYP2A6 diplotype predictive metric, intermediate metabolism compared with slow and normal was a risk factor for smoking frequency and nicotine dependence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, genetic variants in several UGTs are correlated with differences in the glucuronidation of urinary nicotine, cotinine, and 3-hydroxycotinine (24,25). Genome-wide association studies (GWAS) have identified associations between FMO1 and FMO3 SNPs and nicotine dependence (7,19,(26)(27)(28). Previous studies have shown that genetic variations in FMO3 in different smoker cohorts were associated with nicotine dependence (28), while a recent in vivo study demonstrated an association between the FMO3 E308G/E158K haplotype with nicotine-N 0 -oxidation and smoking behavior (29).…”
Section: Introductionmentioning
confidence: 99%